NO sub x emissions from coal combustion - "Sloss, L S" (1991)
The two most important oxides of nitrogen with regard to air pollution are nitric oxide (NO) and nitrogen dioxide (NOsub 2), jointly referred to as NOsub x in the context of this report. Global emissions of NOsub x and of another nitrogen oxide, nitrous oxide (Nsub 2O), are increasing. These gases play important roles in the environment through acidification, forest damage, smog formation, direct and indirect damage to human health, depletion of the stratospheric ozone layer and the greenhouse effect. The report discusses nitrogen chemistry; effects of nitrogen oxides; emission sources and concentrations; transport and deposition of NOsub x; regional emissions, concentrations, and legislation; and impacts of legislation and future NOsub x emissions. 249 refs., 17 figs., 12 tabs.
Keywords: "01 COAL, LIGNITE, AND PEAT"; "54 ENVIRONMENTAL SCIENCES"; "NITROGEN OXIDES"; "AIR POLLUTION"; "ENVIRONMENTAL EFFECTS"; "ACIDIFICATION"; "ATMOSPHERIC CHEMISTRY"; "COAL"; "COMBUSTION"; "DEPOSITION"; "EMISSION"; "ENVIRONMENTAL TRANSPORT"; "FORESTS"; "FOSSIL-FUEL POWER PLANTS"; "GREENHOUSE EFFECT"; "HEALTH HAZARDS"; "NITRIC OXIDE"; "NITROGEN DIOXIDE"; "NITROUS OXIDE"; "OZONE LAYER"; "PLUMES"; "POLLUTION LAWS"; "SMOG"; "SOIL CHEMISTRY"; "TRANSPORTATION SECTOR"; "CARBONACEOUS MATERIALS"; "CHALCOGENIDES"; "CHEMICAL REACTIONS"; "CHEMISTRY"; "ENERGY SOURCES"; "FOSSIL FUELS"; "FUELS"; "HAZARDS"; "LAWS"; "LAYERS"; "MASS TRANSFER"; "MATERIALS"; "NITROGEN COMPOUNDS"; "OXIDATION"; "OXIDES"; "OXYGEN COMPOUNDS"; "POLLUTION"; "POWER PLANTS"; "THERMAL POWER PLANTS"; "THERMOCHEMICAL PROCESSES"; "010900* - Coal, Lignite, & Peat- Environmental Aspects"; "540120 - Environment, Atmospheric- Chemicals Monitoring & Transport- (1990-)"